From Arbia to Nusantara: A Global Cultural Flows Analysis of Arabic Pop Music Consumption in the Arabic Music Lovers Indonesia (AMLI) - Mohammad Fattahun Ni'am, S.Ag., M.A. (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The phenomenon of the growing popularity of Arabic pop music in Indonesia's digital space represents contemporary dynamics in the flow of global cultural circulation. It can be seen from several digital platforms in Indonesia that there are many new Arabic pop music sung by famous musicians such as Amr Diab, Nancy Ajram, Elissa, Sherine, and Kadim Al Sahir. Pop culture products that are also on the rise in the Arab world have succeeded in crossing geographical, linguistic and cultural boundaries through the mediation of digital technology. Many platform of Arabic pop lovers were then born, one of which was Arabic Music Lovers Indonesia (AMLI). This in turn creates cross-regional interactions that are increasingly intense and simultaneous. By utilizing Arjun Appadurai's Global Cultural Flows framework which includes ethnoscapes, mediascapes, technoscapes, financescapes, and ideoscapes, this research examines the consumption, distribution, and reproduction practices of Arabic pop music by the Arabic Music Lovers Indonesia (AMLI) community on social media. The research method used is a qualitative approach through netnography to observe online interactions, enriched by interviews with community members. This approach results in a contextual analysis that not only looks at aspects of music consumption, but also the symbolic and ideological meanings attached to these activities. This research reveals that the consumption of Arabic pop music in the AMLI online community operates as a locus of transnational cultural negotiation, where community members utilize mediascapes and technoscapes to access, distribute and reproduce musical content in a participatory manner. This process not only affirms aesthetic appreciation, but also facilitates the articulation of a collective identity that repositions Arab culture and stereotypes as symbols of modernity and cosmopolitanism that were previously considered pejorative.